Shoulder rotator cuff balance, strength, and endurance in young swimmers during a competitive season - Batalha, N. M.; Raimundo, A. M.; Tomas-Carus, P.; Barbosa, T. M.; Silva, A. J (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to analyze the effects of a competitive swim season on the strength, balance, and endurance of shoulder rotator cuff muscles in young swimmers. A repeated measures design was used with 3 measurements performed during the swim season. A swimmers group (n = 20) of young men with no dry land training and a sedentary group (n = 16) of male students with the same characteristics (age, body mass, height, and maturational state) were evaluated. In both groups, the peak torque of shoulder internal rotator (IRt) and external rotator (ERt) was assessed during preseason, midseason (16 weeks), and postseason (32 weeks). Concentric action at 60 and 180°/s was measured using an isokinetic dynamometer. The ER/IR strength ratios and endurance ratios were also obtained. At 60°/s, there were significant training effects in the IRt strength and ER/IR ratio on both shoulders. This trend was the same throughout the competitive season. The same trend was present at 180°/s because the training effects are seen primarily in IRt and ER/IR ratios. With respect to endurance ratios, within-group data were similar in ERt and IRt for both shoulders, with no significant differences between moments. However, between-group differences occurred mostly in the IRt. Results suggest that a competitive swim season favors the increase of muscular imbalances in the shoulder rotators of young competitive swimmers, mainly because of increased levels of IRt strength and endurance that are proportionally larger than those of their antagonists. A compensatory strength training program should be considered.